REVITALISASI PEMBELAJARAN PENDIDIKAN AGAMA HINDU DI ERA DISTRUPSI DIGITAL - Niluh Ari Kusumawati (Jurnal Pendidikan Agama, 2021)
In the era of digital disruption, the development of science and technology is very rapidly increasingly encouraging reforms in various fields, especially in the field of education in utilizing the results of technology itself in the learning process. Religious education is a compulsory subject that is applied at every level of education. One of them is the learning subject of Hindu religious education. Revitalization of Hindu religious education learning in the era of digital disruption must continue to be encouraged so that superior Hiindu human resources are realized. Educators are currently required to be able to master various technologies so that they are able to use the various learning facilities provided in schools. Educators are required to develop skills by making interactive learning media by utilizing available educational technology. Effective learning requires good planning before the learning process is carried out. Every educator is required to be able to create interactive learning media. Currently, teachers are also required to have various soft skills that can be used to support the learning process. The complex problems in learning Hindu religious education include the system of learners, educators and students. So that innovation and progress in learning Hindu religious education can be realized. Revitalization of Hindu religious education learning is expected to be able to face the challenges of Hindus in the realm of education easily. So that various elements ranging from the younger generation to the elderly can work together to build a better Hindu religious education and create superior Hindu human resources (HR) so that the goals of national education can be achieved.